2022
DOI: 10.1002/ajmg.c.31990
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic focal segmental glomerulosclerosis: A conceptual framework for identification and management of a heterogeneous disease

Abstract: Focal segmental glomerulosclerosis (FSGS) is not a disease, rather a pattern of histological injury occurring from a variety of causes. The exact pathogenesis has yet to be fully elucidated but is likely varied based on the type of injury and the primary target of that injury. However, the approach to treatment is often based on the degree of podocyte foot process effacement and clinical presentation without sufficient attention paid to etiology. In this regard, there are many monogenic causes of FSGS with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 168 publications
(226 reference statements)
0
8
0
Order By: Relevance
“…In addition, accurate diagnosis can prevent the use of ineffective or nephrotoxic treatments, as can occur in individuals with steroid-resistant nephrotic syndrome or FSGS, which often have a genetic etiology. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, accurate diagnosis can prevent the use of ineffective or nephrotoxic treatments, as can occur in individuals with steroid-resistant nephrotic syndrome or FSGS, which often have a genetic etiology. 28…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accurate diagnosis can prevent the use of ineffective or nephrotoxic treatments, as can occur in individuals with steroid-resistant nephrotic syndrome or FSGS, which often have a genetic etiology. 28 Numerous practice guidelines have been issued recommending genetic testing as a first-line diagnostic tool for CKD. 14,22,[29][30][31][32] For example, guidelines for the management of Alport syndrome recommend genetic testing as the gold standard for diagnosis given the improved sensitivity and specificity over kidney biopsy.…”
Section: Effect Of Genetic Testing On Patient Clinical Managementmentioning
confidence: 99%
“…Genetic testing has been recommended for use as an early diagnostic tool for patient evaluation in CKD by multiple expert bodies. 13 , 14 , 15 Recent studies have demonstrated that monogenic causes can be identified in up to 10% of adults and 20%-50% of children with CKD. 13 , 16 , 17 , 18 Furthermore, diagnostic genetic findings have management implications for 26%-95% of patients.…”
Section: How Can Genetic Testing Be Beneficial and What Further Value...mentioning
confidence: 99%
“…Diagnosing genetic FSGS is also challenging. While the most common monogenic causes of FSGS can now be efficiently identified using targeted gene panels, the list of genetic causes is continually expanding (7). Furthermore, it is increasingly apparent that common inherited variants, such as HLA polymorphisms, may also contribute to the risk of primary FSGS (8), which complicates the current definition of genetic FSGS.…”
Section: Introductionmentioning
confidence: 99%